From the Chinese Historiography on Jungars (Journal of history, 2020)
The Jungar factor in geopolitical terms influenced not only on the Kazakh Khanate, but also many countries in Asia, which today are separate independent countries (such as Uzbekistan, Kyrgyzstan, Turkmenistan), as well as such major powers as Russia and China. At studying their history none of the above-mentioned states ignores the problem of relations with Jungaria. However, each country and nation has its own historical knowledge; they have formed their own views on certain historical issues. Therefore, individual countries give different estimates on international policy of the Jungar State. The authors aimed to reveal the main features of Chinese historiography on the history of Jungar khanate. Key words: history, Chinese sources, Jungar Khanate, Chinese historians, research.